2019
DOI: 10.1021/acs.nanolett.9b03484
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Currents at Domain Walls in Multiferroic BiFeO3

Abstract: Multiferroic BiFeO 3 (BFO) films with spontaneously formed periodic stripe domains can generate abovegap open circuit voltages under visible light illumination; nevertheless the underlying mechanism behind this intriguing optoelectronic response has not been understood to date. Here, we make contact-free measurements of light-induced currents in epitaxial BFO films via detecting terahertz radiation emanated by these currents, enabling a direct probe of the intrinsic charge separation mechanisms along with quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
(83 reference statements)
1
45
0
Order By: Relevance
“…disentangles the contributions of different photovoltaic mechanisms in BFO films. [ 212 ] By detecting terahertz radiation emanated by light‐induced currents, the authors found that domain‐wall driven charge separation is the dominant mechanism in BFO films with periodic stripe domains, whereas the BPV effect dominates in the monodomain BFO films. They further revealed that FEDW‐mediated peak photocurrent is two orders of magnitude higher than the BPV‐driven bulk shift current.…”
Section: Topological Structures In Ferroelectric/ferroelastic Thin Fimentioning
confidence: 99%
See 1 more Smart Citation
“…disentangles the contributions of different photovoltaic mechanisms in BFO films. [ 212 ] By detecting terahertz radiation emanated by light‐induced currents, the authors found that domain‐wall driven charge separation is the dominant mechanism in BFO films with periodic stripe domains, whereas the BPV effect dominates in the monodomain BFO films. They further revealed that FEDW‐mediated peak photocurrent is two orders of magnitude higher than the BPV‐driven bulk shift current.…”
Section: Topological Structures In Ferroelectric/ferroelastic Thin Fimentioning
confidence: 99%
“…They further revealed that FEDW‐mediated peak photocurrent is two orders of magnitude higher than the BPV‐driven bulk shift current. [ 212 ] We can see the importance of FEDW plays in the photovoltaic effect, but their exact mechanism is still under debate.…”
Section: Topological Structures In Ferroelectric/ferroelastic Thin Fimentioning
confidence: 99%
“…These inferences are further confirmed by the given relationship of measured main peak amplitude E THz versus E bias . As shown in Figure 4b, with different initial E bias treatment, the E THz shows a similar polarization hysteresis loop in (100) and (110) oriented BFO films, [42] while the E THz versus E bias relationship in (111)-oriented BFO film is linear that is analogous to a nonferroelectric materials. [72] Copyright 2006, American Physical Society.…”
Section: Polarization Dynamicsmentioning
confidence: 74%
“…The last term denotes the oscillation component associated with strain pulse propagation, and 𝜏 0 , T, and ϕ refer to damping time, period, and initial phase of the oscillation, respectively. Based on the Equation (3), the fitted period is ≈29.3 ps, and the strain pulse velocity in [110] direction of BFO film is found to be 4.88 km s −1 . As shown in Figure 8e, the calculated strain pulse velocity is close to velocity (4.76 km s −1 ) that is obtained from thickness-dependent t BFO / STO measurements.…”
Section: Acoustic Phonon Excitations and Strain Propagationmentioning
confidence: 99%
See 1 more Smart Citation